3D printed piezoelectric BNNTs nanocomposites with tunable interface and microarchitectures for self-powered conformal sensors. (November 2020) - Zhang, Jie; Ye, Shibo; Liu, Honglei; Chen, Xiaoliang; Chen, Xiaoming; Li, Baotong; Tang, Wanhong; Meng, Qingcheng; Ding, Peng; Tian, Hongmiao; Li, Xiangming; Zhang, Yanfeng; et al.
Abstract: 3D printing of arbitrary shapes and unique architectures offers unparalleled flexibility and simplicity for fabrication of highly complex 3D conformal electronics. It drives up high demands in electronic materials with excellent processability and functionality simultaneously. Herein, we overcome this challenge in prepared nanofiller/polymer piezoelectric composite by incorporating ultralow loadings (0.2 wt%) of boron nitride nanotubes (BNNTs) in photocurable polymer solution. Furthermore, two effective approaches are introduced to significantly boost the piezoelectric responses through tuning inorganic-polymer interfacial compatibility and structural strain variation. The microstructured piezoelectric composites containing 0.2 wt% functionalized BNNTs exhibits an unprecedentedly high relative sensitivity of (120 mV/(kPa·wt%)) over a broad press region (1–400 kPa), which is 10-fold higher than that of flat composite containing unmodified BNNTs. This dramatic enhancement is ascribed to synergistic contribution from effective stress transfer efficiency between strong piezoelectric BNNTs and nonpiezoelectric polymers, and the improved structural strain variations by topology optimization of microstructures. The as-printed piezoelectric materials are successfully demonstrated as self-powered and conformal tactile sensor array to enable haptic sensing of robotic hand and detect spatial distribution of force on uneven surfaces. Our works provide a promising route for design and fabrication of novel conformal electronics with target performance by high-resolution 3D printing from rational design of materials to optimization of microstructures topology. Graphical abstract: A high performance, light-weight, 3D conformal piezoelectric sensor based on micropatterned BNNTs/photocurable polymer composites are designed and fabricated by micro 3D printing technique. By modulating interfacial compatibility and structural strain variation, an order of magnitude enhancement of the piezoelectric performance in the 3D-printed device is successfully achieved, which demonstrates an unprecedentedly high relative sensitivity of (120 mV/(kPa·wt%)) over a broad press region. Image 1 Highlights: PSLA-based micro 3D printing is a promising technique for the fabrication of conformal electrons with unique 3D architectures. 3D printable nanocomposites with ultralow loading (0.2 wt%) of BNNTs demonstrates excellent piezoelectric properties. Surface functionalization and structural topology optimization significantly boost piezoelectric performance of composites. The micropatterned nanocomposite films exhibit an unprecedentedly high relative sensitivity over a broad press region.